Founding Territorial Cults in Early Japan: Traces of a Forgotten Ritual in Ancient Myths and Legends - Domenig, Gaudenz (Asian Studies E-Books Online, Collection 2024, 2023)
"The first book that deals with the territorial cults of early Japan by focusing on how such cults were founded in ownerless regions. Numerous ancient Japanese myths and legends are discussed to show that the typical founding ritual was a two-phase ritual that turned the territory into a horizontal microcosm, complete with its own 'terrestrial heaven' inhabited by local deities. Reversing Mircea Eliade's popular thesis, the author concludes that the concept of the human-made horizontal microcosm is not a reflection but the source of the religious concept of the macrocosm with gods dwelling high up in the sky. The open access publication of this book has been published with the support of the Swiss National Science Foundation"--